Expanding RNA editing toolkit using an IDR-based strategy - Minghui Di; Junjun Lv; Zhengyu Jing; Yijie Yang; Kunlun Yan; Jianguo Wu; Jianyang Ge; Simone Rauch; Bryan C. Dickinson; Tian Chi (Elsevier, 2024)
RNA base editors should ideally be free of immunogenicity, compact, efficient, and specific, which has not been achieved for C > U editing. Here we first describe a compact C > U editor entirely of human origin, created by fusing the human C > U editing enzyme RESCUE-S to Cas inspired RNA targeting system (CIRTS), a tiny, human-originated programmable RNA-binding domain. This editor, CIRTS-RESCUEv1 (V1), was inefficient. Remarkably, a short histidine-rich domain (HRD), which is derived from the internal disordered region (IDR) in the human CYCT1, a protein capable of liquid-liquid phase separation (LLPS), enhanced V1 editing at on-targets as well as off-targets, the latter effect being minor. The V1-HRD fusion protein formed puncta characteristic of LLPS, and various other IDRs (but not an LLPS-impaired mutant) could replace HRD to effectively induce puncta and potentiate V1, suggesting that the diverse domains acted via a common, LLPS-based mechanism. Importantly, the HRD fusion strategy was applicable to various other types of C > U RNA editors. Our study expands the RNA editing toolbox and showcases a general method for stimulating C > U RNA base editors.